Affective responses after different intensities of exercise in patients with traumatic brain injury - Rzezak, Patricia; Caxa, Luciana; Santolia, Patricia; Antunes, Hanna K. M.; Suriano, Italo; Tufik, Sérgio; de Mello, Marco T. (Frontiers in Psychology, 2015)
BACKGROUND: Patients with traumatic brain injury (TBI) usually have mood and anxiety symptoms secondary to their brain injury. Exercise may be a cost-effective intervention for the regulation of the affective responses of this population. However, there are no studies evaluating the effects of exercise or the optimal intensity of exercise for this clinical group. METHODS: Twelve male patients with moderate or severe TBI [mean age of 31.83 and SD of 9.53] and 12 age- and gender-matched healthy volunteers [mean age of 30.58 and SD of 9.53] participated in two sessions of exercise of high and moderate intensity. Anxiety and mood was evaluated, and subjective assessment of experience pre- and post-exercise was assessed. A mixed between and within-subjects GLM analysis was conducted to compare groups [TBI, control] over condition [baseline, session 1, session 2] allowing for group by condition interaction to be determined. Planned comparisons were also conducted to test study hypotheses. RESULTS: Although no group by condition interaction was observed, planned comparisons indicated that baseline differences between patients and controls in anxiety (Cohens’ d=1.80), tension (d=1.31), depression (d=1.18), anger (d=1.08), confusion (d=1.70), psychological distress (d=1.28) and physical symptoms (d=1.42) disappear after one session of exercise, independently of the intensity of exercise. CONCLUSIONS: A single-section of exercise, regardless of exercise intensity, had a positive effect on the affective responses of patients with TBI both by increasing positive valence feelings and decreasing negative ones. Exercise can be an easily accessible intervention that may alleviate depressive symptoms related to brain injury.